Uncoiling Host–Parasite Interrelationships: Bounded Snail‐Host Flexibility Amid Conserved Trematode Morphology - Taylor M. Fiedor; Samuel N. Messinides; Kyle D. Gustafson (Molecular Ecology, 2026)
Host–parasite communities are shaped by the tension between evolutionary constraints and ecological opportunity. Digenetic trematodes, which rely on snail hosts to produce diverse larval stages, offer a powerful system to test hypotheses about evolutionary conservatism and ecological flexibility with implications for community structure. Across 120 sites spanning three ecoregions, 6.5% of 14,623 snails were infected by trematodes. Sequencing (18S and 28S) from 104 cercariae among 12 morphotypes revealed 22 trematode families concentrated in a few keystone host taxa. Model‐based analyses showed that cercaria morphotypes exhibited nearly perfect phylogenetic signal. In contrast, host use, defined by the snail lineages each trematode infects, evolves under an Ornstein–Uhlenbeck model of stabilizing selection. This asymmetry indicates that cercaria morphotypes are evolutionarily stable relative to host use, which remains flexible but bounded within an adaptive landscape. Our data elucidate complex life cycles, uncovers parasite diversity maintained by keystone host taxa and reveals recurrent ‘evolutionary reunions’, in which distantly related trematodes revisit ancestral snail associations through ecological fitting and adaptations toward common host lineages. Evolutionary reunions help resolve the long‐standing parasite paradox—how parasites remain specialized yet occasionally capture or shift hosts—by demonstrating that host–parasite evolution is not a linear process of continual novelty but a dynamic interplay of constraint, contingency and opportunity. Together, these findings provide a molecular framework linking evolutionary and ecological processes to identify general rules of symbiotic interrelationships, with implications for predicting the origins of emerging diseases, the persistence of coevolutionary networks and biodiversity responses to environmental change.

Mitogenomics reveals low variation within a trigeneric complex of black corals from the North Pacific Ocean - Yessenia M. Bledsoe-Becerra; Iesha S. Whittaker; Jeremy Horowitz; Katherine Medina Naranjo; Jicayla Johnson-Rosemond; Kristen H. Mullins; Karena M. Cunningham; Suchir Shetty; Samuel N. Messinides; Melinda S. Behney; Jessica A. Fehsal; Ashley N. Watson; et al. (Organisms Diversity & Evolution, 2022)